Dissolution of particulate phosphorus in pig slurry through biological acidification: A critical step for maximum phosphorus recovery as struvite. (1st November 2017) - Piveteau, Simon; Picard, Sylvie; Dabert, Patrick; Daumer, Marie-Line
Abstract: Recycling phosphorus as struvite from pig slurry requires an acidification step to dissolve the inorganic solids containing most of the phosphorus. This study focused on the biological acidification of several pig slurries using sucrose as a model organic co-substrate. Lactic acid fermentation occurred systematically, dissolving 60–90% of TP (total phosphorus) and T-Mg (total magnesium) at pH 6 or lower. Optimal pH range for maximum P dissolution aimed at struvite recovery was 5.5–6. A simple model was developed correlating pH, sucrose and buffer capacity to optimize P dissolution and future recovery using real organic waste. Graphical abstract: Highlights: Accumulation of lactic acid during anaerobic degradation of sucrose in pig slurry. Secondary fermentation degrading lactic acid into other compounds at pH above 5.5. Dissolution of 60–90% of TP at pH 6 and below. Strong correlation between sucrose added, buffer capacity, initial and final pH.